Analysis of Customer Perceptions of Security and Ease of Transactions Using the BRImo Application at the BRI Nunukan Branch (Pusat Riset dan Inovasi Nasional, 2026)
This study examines users' perceptions of security and convenience in using the BRImo mobile banking application at BRI Nunukan Branch, a digital financial service increasingly relied upon for daily transactions. Despite rapid digitalization in the banking sector, many users still express concerns regarding data protection, transaction safety, and the reliability of mobile banking features. Therefore, this research aims to explore in depth how BRImo users evaluate the security and convenience of the application, and what factors influence their overall experience. This study employs a qualitative case study approach involving 30 active BRImo users selected using purposive sampling. Data were collected through in-depth interviews, direct observation of application usage, and documentation, then analyzed using the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The findings indicate that BRImo is generally perceived as secure due to layered security features such as PIN, password, OTP, and fingerprint authentication, supported by BRI's internal monitoring system for suspicious transactions. However, some users still experience minor issues such as delayed OTP or temporary account blocking. In terms of convenience, the majority of respondents consider BRImo easy to use, with intuitive menus and fast transaction processes, although challenges remain among new users and those facing unstable internet connections. These findings demonstrate that both security and convenience significantly shape user trust and satisfaction. This research contributes to a deeper understanding of digital banking adoption in non-urban settings, emphasizing the role of user experience in strengthening digital service engagement. The study concludes that BRImo provides adequate security and high convenience, while recommending continuous system improvement and customer education to enhance digital transaction safety and usability.